Feeding practices during the first Eighteen months of life - Sithamparapillai, K.; Samaranayake, D.; Wickramasinghe, V.P. (The Nutrition Society of Sri Lanka, 2021)
Inappropriate feeding practices during early life are the main causes of child malnutrition. The objective of this study was to determine the feeding practices of children 12 - 18 months of age and their association with growth faltering. A cross-sectional descriptive study was conducted among 254 children aged 12 and 18 months attending an immunization clinic of a tertiary hospital. Feeding practices were assessed using interviewer-administered questionnaire. Weight and length were measured using standard methods. Data on past growth were extracted from the Child Health Development Record. There were 44.5% (n=113) girls, and 53.1% (n=135) were 12-month-olds. 20.7% (n=28) of the 12 month-olds and 14.3% (n=17) of the 18 month-olds had weight-for-length <-2SD. Exclusive breastfeeding was given at least 4 months to 87.8% (n=223) and at least 6 months to 60.2% (n=153). 91.9% (n=124) of the 12 month- olds were still breastfed. Of them, 41.9% (n=52) were breastfed on-demand (<-1SD; p=0.06) and 42.7% (n=53) were given several feeds during the night (<-1SD; p=0.09) therefore these practices were not significantly associated with nutritional status. 84% (n=100) of the 18 month-olds were still breastfed. Of them, 43% (n=43) were still breastfed on-demand and this was not significantly associated with nutritional status. Several night feeds were given to 51.2% (n=61) of the 18 month-olds and this was significantly associated with weight-for-age <-2SD (p=0.04) and weight-for-length <-2SD (p=0.006). 32.6% (n=44) of the 12 month-olds and 25.2% (n=30) 18 month-olds were on formula feeds which showed no association with the nutritional status. Introduction of foods of animal origin were delayed. Eggs, fish and meat were not given till 8 months to 44.8% (n=114), 32.7% (n=83) and 68.9% (n=175), respectively. Inappropriate feeding practices are prevalent in this population with high prevalence of growth faltering at 18 months of age.
Keywords: Children; Feeding practices; Growth faltering